Epic Victories and Failures: Homer and Vergil in Russia. (9th January 2021) - Kalb, Judith E.; Torlone, Zara M.
Abstract: This article focuses on selected complete Russian verse translations of Homer's Iliad and Odyssey and of Vergil's Aeneid produced over a period of nearly two centuries. By focusing on translation approach and goals, historical and cultural circumstances, and the literary talent of the translators, the authors explore the reasons for a particular translation's success or failure. Further, they address the question of how Russian translators achieved canonical, or generally accepted, translations of the Homeric epics, while translations of Vergil's epic found no such success.